The Impact of Workforce Diversity Management on Organizational Performance: A Study in Nepalese Hospitality Sector - Rijal, Rheet (Quest Journal of Management and Social Sciences, 2023)
Background: The 1960s and 1970s in the United States marked a pivotal era in recognising the importance of workplace diversity and equal opportunities, leading to the establishment of the President's Committee on Equal Employment and the enactment of the 1964 Civil Rights Act. This historical backdrop has evolved into a contemporary emphasis on diverse dimensions, such as demographic, cultural, and cognitive aspects, underscoring its critical role in improving organisational performance—an insight extended to the study's focus on Nepal's hospitality sector. Objectives: This research aims to investigate the impacts of workplace diversity on organisational performance with the mediating role of inclusion and employee engagement solely. Methods: The study followed a positivist research paradigm, deductive reasoning, a causal-comparative research method, and snowball sampling techniques for its procedural operations. The study's target populations were the staff employed in hospitality sectors in Nepal. The study incorporated 439 as a sample size. The structured survey questionnaire was used to collect the primary data. The data were analysed using descriptive and inferential statistics like percentages, frequency, and structural equation modelling. In order to analyse the data, SPSS 20 and AMOS 22 were used. Results: The study supports hypotheses related to the positive influence of workforce diversity on employee inclusion, the positive effects of employee inclusion and engagement on organisational performance, and the partial mediation role of both employee inclusion and engagement in the relationship between workforce diversity and organisational performance. However, the study rejects hypotheses suggesting a direct impact of workforce diversity on employee engagement and organisational performance in the Nepalese hospitality sector. Conclusions: The crucial role of fostering employee inclusion positively impacts loyalty and effort. While workforce diversity may not directly impact organisational performance, focusing on inclusion can lead to better outcomes. Organisations are urged to prioritise creating inclusive environments for enhanced employee commitment and to better align with the needs of a diverse customer base. Implications: This research benefits human resource (HR) managers and businesses as it furnishes information that can be utilised to enhance legislative frameworks and establish measures for monitoring employee diversity policies. The findings of this study also aid established and emerging businesses in determining crucial considerations related to staff diversity. Employees currently employed will benefit from this research as it sheds light on the significance of staff diversity in terms of organisational success and growth. Paper type: Research Paper Key Words: Quantitative research, Diversity management, Gender, Age, Hospitality.